2022
DOI: 10.1186/s12889-022-12532-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial impacts of home-schooling on parents and caregivers during the COVID-19 pandemic

Abstract: Background The COVID-19 pandemic has been highly disruptive, with the closure of schools causing sudden shifts for students, educators and parents/caregivers to remote learning from home (home-schooling). Limited research has focused on home-schooling during the COVID-19 pandemic, with most research to date being descriptive in nature. The aim of the current study was to comprehensively quantify the psychosocial impacts of home-schooling on parents and other caregivers, and identify factors as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 14 publications
(17 reference statements)
4
39
1
6
Order By: Relevance
“…Furthermore, other Australian cross-sectional studies of general samples conducted during the COVID-19 pandemic have indicated better wellbeing than our tourism operator cohort. One found mean WHO-5 scores of 51.4 (SD 23.2) ( Cornell et al, 2021 ) and another between 50.4 (SD 23.98) and 52.0 (SD 25.1) in adults with and without children to home-school ( Calear et al, 2022 ). This suggests that SME tourism operators in Victoria were particularly low.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other Australian cross-sectional studies of general samples conducted during the COVID-19 pandemic have indicated better wellbeing than our tourism operator cohort. One found mean WHO-5 scores of 51.4 (SD 23.2) ( Cornell et al, 2021 ) and another between 50.4 (SD 23.98) and 52.0 (SD 25.1) in adults with and without children to home-school ( Calear et al, 2022 ). This suggests that SME tourism operators in Victoria were particularly low.…”
Section: Discussionmentioning
confidence: 99%
“…Bubb and Jones (2020) agree that parents have to shoulder a higher degree of responsibility in the education of their children. Despite parents having to shoulder the responsibility of home-schooling, they also experienced challenges such as content knowledge of the curriculum, use of technology, socio-economic conditions and a balance between working from home and home-schooling (Calear et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…treffen. Dies deckt sich mit einer Reihe von Studien zu den negativen Auswirkungen der Corona-bedingten Schulschließungen auf das Lernen aus den verschiedensten Ländern wie Australien [6], Deutschland [59], Indien [39] oder Norwegen [10]…”
Section: Theorieunterricht In Fahrschulenunclassified